ANALISIS STRATEGI BRANDING DAN PENINGKATAN KUALITAS UMKM MELALUI DIGITALISASI KEUANGAN DAN LEGALISASI PRODUK - Yuli Ermawati; Pujianto Pujianto; Nurleila Jumati (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
Along with technological developments and the dynamics of the business world, more and more MSMEs are realizing that conventional business approaches are no longer sufficient. Changes in consumer behavior that are now digital are encouraging business actors to start transforming, in order to remain relevant and competitive in an ever-changing market. The purpose of this activity is to map a village branding strategy through MSMEs, and to upgrade the class of village MSMEs through Financial Digitalization and Product Legalization. The long-term goal is for business sustainability and upgrade the class of MSMEs in the RW VI Pakal area with the assistance of Karang Taruna colleagues as the successors of the activity. The method used is the Implementation Method consisting of preparation, implementation, monitoring and evaluation, and program sustainability. The results of this activity, through a SWOT Analysis, the PPM Team together with Karang Taruna discovered a Village Branding Strategy through MSMEs by highlighting the village's superior products and forming MSME groups under the management of Karang Taruna. In addition, through socialization and coaching for financial digitalization, product legalization, and digital marketing, the PPM Team accompanies MSMEs to upgrade their class.